EDUCATORS’ PERSPECTIVES ABOUT ICT ENABLED TEACHING - Dube, Sibusisiwe (PEOPLE: International Journal of Social Sciences, 2017)
The availability of Information and Communication Technologies (ICT) in education has not translated to pedagogical use in Higher Education Institutions (HEI), particularly in the developing nations context where use of ICT based paradigms like e-learning is invisible. This study investigated the educators’ perspectives about ICT enabled teaching strategies by employing quantitative and qualitative data collection instruments. Findings revealed that despite valuing these strategies, educators have institutional and technological concerns requiring redress. Contrary to existing literature, generation gap, ICT literacy and individual values had no effect to the way the cohort perceives ICT based teaching. Instead, university’s’ structures, management decision making and the ICT implementation culture were major themes emerging from this study, as the source of the sporadic ICT utilization that translates to the second order digital divide, a problem of concern both in theory and practice.